Pengaruh Audit Mutu Internal, Kepemimpinan, dan Komitmen Madrasah Terhadap Kualitas Pelayanan di MAN 1 Lamongan - A Khudori; Umar Burhan; Suharto Suharto (Pusat Riset dan Inovasi Nasional, 2025)
. This study aims to determine and analyze the influence of internal quality audits, leadership, and madrasah commitment on service quality at MAN 1 Lamongan. In an era of increasingly fierce competition in education quality, madrasahs are required to continuously improve and innovate their educational services. Internal quality audits are an important tool for identifying the strengths and weaknesses of an institution, while effective leadership and madrasah commitment are the main pillars in fostering a culture of sustainable quality. This study uses a quantitative approach with a survey method, where data is collected through the distribution of questionnaires to all educators and educational staff at MAN 1 Lamongan. The data analysis technique used is multiple linear regression to determine the relationship between independent variables (internal quality audit, leadership, and madrasah commitment) and dependent variables (service quality). The results of the study indicate that simultaneously, all three independent variables have a significant influence on service quality. Partially, internal quality audit has a positive influence through improved evaluation systems and continuous improvement. Effective leadership creates a conducive work environment and encourages active participation from all madrasah components. Meanwhile, the madrasah's high commitment to the institution's vision and mission further strengthens efforts to provide excellent service to students and the community. Thus, collaboration between the audit system, leadership, and madrasah commitment is a key factor in improving the quality of educational services at MAN 1 Lamongan. This study recommends the importance of strengthening quality management capacity and consistently involving all madrasah components in the process of improving service quality.